Estudos dos mecanismos envolvidos no efeito protetor da sinvastatina na periodontite experimental em ratos - Dalcico, Roberta (2013)
Simvastatin is a cholesterol-lowering drug whose pleiotropic effects may have therapeutic impact in bone diseases. The purpose of this study was to evaluate the effect of simvastatin on rats subjected to experimental periodontal disease (EPD). Periodontitis was induced by ligature placement around the upper second left molar of Wistar rats for 11 days. Groups of six animals received via oral (gavage) either saline or simvastatin (3, 10 and 30 mg/kg/day) until the sacrifice on the 11th day. Alveolar bone loss was determined by macroscopic and histologic examination. Aspartate aminotransferase (AST), alanine aminotransferase (ALT) and total alkaline phosphatase (TAP) serum levels were evaluated. We also analyzed the myeloperoxidase (MPO) activity and the levels of interleukin-1β (IL-1 β), tumor necrosis factor-α (TNF-α), interleukin-10 (IL-10), reduced glutathione (GSH), malonylaldehyde (MDA) and nitrate/nitrite (NOx) in the gingival tissue. Expression of inducible nitric oxide synthase (iNOS), matrix metalloproteinase 1 and 8 (MMP-1/8), bone morphogenetic protein-2 (BMP-2), osteoprotegerin (OPG), receptor activator of nuclear factor kappa-B (RANK) and receptor activator of nuclear factor kappa-B ligand (RANKL) was investigated in the periodontium by immunohistochemistry. Nuclear factor kappa-B (NFκ-B) activation was measured by determination of p50 in the gingivae by western blot. Treatment with simvastatin improved alveolar bone structure loss in all parameters studied, showing anti-inflammatory and antioxidant activity. In addition, simvastatin reduced expression of iNOS, MMP-1/8, RANK, RANKL and NFκ-B, as well as enhanced the levels of OPG and BMP-2 in the periodontal tissues. Simvastatin (30 mg/kg) was also able to increase the activity of TAP at 11th day, when compared to the group of untreated animals (saline). No differences were found in the levels of AST and ALT for all groups studied. Altogether our data suggest that simvastatin prevent inflammatory bone resorption in experimental periodontitis, which may be mediated by its anti-inflammatory and antioxidant properties.